Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi Dengan Metode SAW ( Studi Kasus SDN Kedunglumbu) - Andhika Dias F; Dandi Riski Saputra; Fajar Bagus Saputra; Naufaldi Rizqi Eka P; Rahmat Nur Shidi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
This study develops a Decision Support System (DSS) for selecting outstanding students at SDN Kedunglumbu using the Simple Additive Weighting (SAW) method. The main goal of this DSS is to help the school determine outstanding students more objectively and efficiently. The SAW method was chosen for its ability to provide weighted sums of relevant criteria, ensuring accurate and fair decisions. The system development follows a waterfall approach, with structured stages from planning to implementation. The evaluation criteria include PPKN, Indonesian Language, Science, Social Studies, and Mathematics, with seven students as the evaluated alternatives. The implementation of the DSS successfully displays information about outstanding students clearly, with Natasha Cahya Putri Ayu selected as the outstanding student with the highest preference score of 0.786. System testing using the blackbox testing method confirms that the system operates as expected, and calculations using the SAW method are consistent with manual calculations. Overall, the developed DSS successfully facilitates the selection process of outstanding students efficiently and objectively, while the SAW method proves effective in providing reliable results and supporting better decision-making in the educational environment.